The historiography of Alexander the Great - Nawotka, Krzysztof; Rollinger, Robert; Wiesehöfer, Josef; Wojciechowska, Agnieszka (Classica et orientalia, 2018)
Historiography of Alexander the Great : an introduction / Krzysztof Nawotka, Josef Wiesehöfer and Agnieszka Wojciechowska -- Alexandre à Troie : images, mythe et realia / Pierre Briant -- Of philosophers and kings : concerning Philip II of Macedon's alleged "debt" to Plato / Kenneth R. Moore -- Patron the Phocian : a written "mercenary source"/ Nicolas Sekunda -- On the traces of Onesicritus. Some historiographical aspects of Alexander's Indian campaign / Reinhold Bichler -- Alexander and the palace of Memnon / Adam Łukaszewicz -- Cleomenes of Naucratis in pseudo-Aristotle's Oeconomica and the topoi of the ancient Egyptian propaganda / Ivan Ladynin -- P.OXY. 4808 and Historians / Robin Lane Fox -- Agatharchides of Cnidus and the idea of a peripatetic view of Alexander / Gościwit Malinowski -- In search of the many images of Alexander at Chaeronea. Historical and literary traditions in Plutarch's Corpus / Federicomaria Muccioli -- The miracles of water and oil in the historiography on Alexander / Sabine Müller -- The subtle and red line between reality and fiction : Alexander and his 'propaganda machine' / Giuseppe Squillace -- I Maccabees and the Alexander Romance / Krzysztof Nawotka -- Alexander and Caligula in the Jerusalem temple : a case of conflated traditions / Ory Amitay -- The Alexander historians in Byzantium / Corinne Jouanno.